(untitled) (Research, Society and Development, 2021)
The objective of article is to conduct a bibliographic review of studies related to the privatization of the National Health Service (SUS) in Brazil, organizing the state-of-the-art on the topic and indicating possible existing gaps on the subject, using Scielo database, between the years 1998 and 2020. Bibliometric metrics and Social Network Analysis were also used to support the discussion of results. The results show that a significant part of articles was published between 2011 and 2020. FIOCRUZ is the main institution associated with the authors of the sample. The main scientific journals in terms of number of published articles and in relation to the h5 index are Cadernos de Saúde Pública and Ciência & Saúde Coletiva, respectively. It is observed among the scientific journals the relevance of the collective health area for studies on privatization of the SUS and, as a minority, the contributions of economics, social work and psychology to the development of the theme. The keywords network shows the terms with the highest occurrences among the articles in the sample. As for the network between the articles and the analysis groups of the privatizing elements of the SUS, it was identified that the management, financing and political-institutional framework analysis groups are the most studied, and the groups related to professional training and labor relations, social participation and comparative analysis are little addressed by the articles of the sample, thus representing an interesting path for the development of new studies related to the privatizing elements of the SUS.